Growth and tolerance of healthy, term infants fed lower protein extensively hydrolyzed or amino acid-based formula: double-blind, randomized, controlled trial - Craig B. Adams; William H. Johnston; Harold Deulofeut; Joseph Leader; Robbie Rhodes; Michael Yeiser; Cheryl L. Harris; Jennifer L. Wampler; Rebecca J. Hill; Timothy Cooper (BMC, 2021)
Abstract Background Optimal protein level in hypoallergenic infant formulas is an area of ongoing investigation. The aim was to evaluate growth of healthy term infants who received extensively hydrolyzed (EH) or amino acid (AA)-based formulas with reduced protein. Methods In this prospective, multi-center, double-blind, controlled, parallel group study, infants were randomized to receive a marketed EH casein infant formula at 2.8 g protein/100 kcal (Control) or one of two investigational formulas: EH casein formula at 2.4 g protein/100 kcal (EHF) or AA-based formula at 2.4 g total protein equivalents/100 kcal (AAF). Control and EHF each had 2 × 107 CFU Lactobacillus rhamnosus GG/100 kcal. Anthropometrics were measured and recall of formula intake, tolerance, and stool characteristics was collected at 14, 30, 60, 90, 120 days of age. Primary outcome was weight growth rate (g/day) between 14 and 120 days of age (analyzed by ANOVA). Medically confirmed adverse events were recorded throughout the study. Results No group differences in weight or length growth rate from 14 to 120 days were detected. With the exception of significant differences at several study time points for males, no group differences were detected in mean head circumference growth rates. However, mean achieved weight, length, and head circumference demonstrated normal growth throughout the study period. No group differences in achieved weight or length (males and females) and head circumference (females) were detected and means were within the WHO growth 25th and 75th percentiles from 14 to 120 days of age. With the exception of Day 90, there were no statistically significant group differences in achieved head circumference for males; means remained between the WHO 50th and 75th percentiles for growth at Days 14, 30, and 60 and continued along the 75th percentile through Day 120. No differences in study discontinuation due to formula were detected. The number of participants for whom at least one adverse event was reported was similar among groups. Conclusions This study demonstrated hypoallergenic infant formulas at 2.4 g protein/100 kcal were safe, well-tolerated, and associated with appropriate growth in healthy term infants from 14 to 120 days of age. Trial registration ClinicalTrials.gov, ClinicalTrials.gov Identifier: NCT01354366 . Registered 13 May 2011.